Atomistic investigation of effect of twin boundary on machinability in diamond cutting of nanocrystalline 3C-SiC - Liang Zhao; Weimian Guan; Jiwen Xu; Zhiyuan Sun; Maoda Zhang; Junjie Zhang (AIMS Materials Science)
The machinability of hard brittle nanocrystalline cubic silicon carbide (3C-SiC) is strongly dependent on internal microstructure and its adapted machining response. Here, we conducted molecular dynamic simulations to explore the machinability of nanotwinned 3C-SiC with a large number of twin boundaries in diamond cutting. The effect of the introduction of twin boundaries on the diamond cutting of nanocrystalline 3C-SiC, particular for its contribution to suppressing brittle fracture and improving ductile-mode cutting, was investigated in-depth. Our simulation results revealed that twin boundaries exerted a significant impact on the deformation mechanism and subsequent surface integrity of nanocrystalline 3C-SiC. Specifically, intergranular fracture was significantly suppressed by the introduction of twin boundaries. In addition, various deformation behaviors such as phase transformation, crack propagation, dislocation activity, and twin boundary-associated deformation mechanisms were operated in cutting process of nanotwinned 3C-SiC. Furthermore, the influence of twin boundary spacing on the diamond cutting characteristics of nanotwinned 3C-SiC was also addressed.